2020
DOI: 10.3389/fmars.2020.00640
|View full text |Cite
|
Sign up to set email alerts
|

Stock Status Assessments for 12 Exploited Fishery Species in the Tsushima Warm Current Region, Southwest Japan and East China, Using the CMSY and BSM Methods

Abstract: This contribution presented stock assessments for 10 fish and 2 squid populations exploited by Chinese, South Korean, and Japanese fishing fleets in the Tsushima Warm Current region, i.e., Southwest Japan and East China. The methods used were a Monte Carlo method (CMSY) and a Bayesian state-space implementation of the Schaefer model (BSM), based on published time series of catch and abundance data (SSB and CPUE). Results showed that 2 fish stocks, Japanese jack mackerel (Trachurus japonicus) and yellowback sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Such a comprehensive review is a valuable trial for East Asian countries, as the beginning toward modern fisheries stock assessment and management. We also agree with one of the main conclusions drawn by Wang et al (2020b) (hereafter "WA2020"), emphasizing the importance of close cooperation among East Asian countries for stock assessment and management.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Such a comprehensive review is a valuable trial for East Asian countries, as the beginning toward modern fisheries stock assessment and management. We also agree with one of the main conclusions drawn by Wang et al (2020b) (hereafter "WA2020"), emphasizing the importance of close cooperation among East Asian countries for stock assessment and management.…”
Section: Introductionsupporting
confidence: 88%
“…(A) shows stocks which the selection of abundance indices leads to misunderstanding of current stock status, and (B) shows stocks which the selection of abundance indices does not affect the current stock status estimation, but still leads to different view of past trajectories. We found such insufficient use of abundance indices in seven stocks by Wang et al (2020b), but could re-produce the same results for only six stocks as shown above.…”
Section: Inappropriate Use Of Relative Abundancesupporting
confidence: 75%
See 3 more Smart Citations